Quantitative Multi-Scale Operando Diagnosis of Water Localization inside a Fuel Cell. Issue 2 (1st January 2017) - Morin, A.; Gebel, G.; Porcar, L.; Peng, Z.; Martinez, N.; Guillermo, A.; Lyonnard, S.
Abstract : We report on a quantitative method to diagnose water distribution at various relevant length scales inside an operating proton membrane exchange fuel cell (PEMFC). By means of Small Angle Neutron Scattering experiments designed to achieve unprecedented spatial and temporal resolutions, we provide the first mapping of local water quantity, simultaneously over the entire cell as well as inside the polymer membrane, and we analyze the observed heterogeneities in light of various functional parameters. We evidence non-homogeneous water distribution at the scale of the flow field pattern, with significant differences in water content in front of the channel and the ribs, both inside and outside the membrane, depending on the positions close to gas inlet or gas outlet. In particular, it is shown that the amount of liquid water outside the membrane and the hydration state of the membrane are not directly cross-correlated. The operando water mapping at the level of the unit fuel cell allows us to identify the major phenomena controlling water formation and/or accumulation, therefore providing unique insights to improve the complex operando behavior of a fuel cell.